Epidemiological Study of Organophosphorus Poisoning at a Tertiary Care Hospital of Central Nepal - Pradhan, Manohar; Upadhyay, Hari Prasad; Shrestha, Ayasha; Pradhan, Alok (Journal of College of Medical Sciences-Nepal, 2022)
Introduction: Poisoning is an acute medical emergency. Organophosphorus (OP) poison, being easily available and relatively cheaper, is mostly used by people for suicide. It is a major health problem worldwide also a major cause of suicide in Nepal. The purpose of this study was to assess the overall profile of patients with Organophosphorus (OP) poisoning. Methods: A Prospective hospital based descriptive cross-sectional study was conducted on patients of organophosphorous poisoning in the emergency department (ER) of College of Medical Sciences and Teaching Hospital during one year period from 1st January 2020 to 31st December 2021. Data analysis was done using SPSS-16 software. Categorical variables were presented in the form of tables with frequency and percentage. Data was analyzed by using descriptive statistical tools. Results: A total of 123 OP poisoning cases attended in the emergency department of College of Medical Sciences over a period of one year. The overall female to male ratio was 1.19:1. Most poisoning occurred in the age group 15-25yrs. Majority of the patients were married and were students. Oral route (87.83%) was the most common route of administration. The main reason was family and personal issues. Majority of the patients stay 3-7 days in the hospital. The mortality of poisoning was 3.25%. Conclusions: Majority of the intentional poisoning occurred in the female, married & students of younger age group. The main reason was family and personal issue.